Produtividade da soja após reimplantação de pastagem degradada com e sem fosfatagem - Feba, Luanda Torquato (2016)
The objective of this research was to evaluate the effect of different forms of grazing reimplantation with and without phosphating in soybean productivity. The experiment was conducted at the Experimental Farm of the University of West Paulista (UNOESTE), located in the municipality of Presidente Bernardes - SP, January 2014 to February 2015. It was conducted in a split plot design in tracks, with four replications. The plots consisted of four grazing reimplantation systems with 4 kg ha-1 Urochloa brizantha (grass - Marandu) (Natural Bank Seed (BNS); BNS + Sowing the haul; BNS + Seeding online; BNS + Seeding in line intercropped with soybeans) and subplots (with and without phosphorus fertilization). The variables analyzed were: number of tillers and dry matter yield (PMS); analysis of plant tissue pasture; chemical analysis of the pasture; Leaf analysis analysis in soybean; production of components and soybean productivity. The variables analyzed in each treatment were submitted to analysis of variance (p <0.05) and the means were compared by Tukey test (p <0.05) through Sisvar software. In this context, it can be concluded that the soybean yield was higher with the reintroduction of grazing intercropped with soybean. This treatment led to an increase of 276 kg ha-1 in relation to the treatment that there was no grazing reimplantation (BNS). Phosphate Fertilization increased the phosphorus content in the soil; in the dry matter production of soybean; the leaf phosphorus content and productivity of soybean.